2020
DOI: 10.3389/fimmu.2020.00828
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Production in Murine Polymicrobial Sepsis—Kinetics and Key Players

Abstract: Although antigen-specific priming of antibody responses is impaired during sepsis, there is nevertheless a strong increase in IgM and IgG serum concentrations. Using colon ascendens stent peritonitis (CASP), a mouse model of polymicrobial abdominal sepsis, we observed substantial increases in IgM as well as IgG of all subclasses, starting at day 3 and peaking 2 weeks after sepsis induction. The dominant source of antibody-secreting cells was by far the spleen, with a minor contribution of the mesenteric lymph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…We and others have shown that sepsis induced a marked increase in serum IgM levels followed by an even stronger IgG response (11,13). As we have previously shown, most ASCs reside in the spleen, and the class switch to IgG results from both TI and TD processes (14). Since the antigen-specific T cell response is still fully functional at the onset of sepsis (47), we assumed that the class switched IgG response was mainly directed at the invasive bacteria.…”
Section: A Strong Induction Of Total Serum Igg During Sepsis Was Not mentioning
confidence: 97%
See 4 more Smart Citations
“…We and others have shown that sepsis induced a marked increase in serum IgM levels followed by an even stronger IgG response (11,13). As we have previously shown, most ASCs reside in the spleen, and the class switch to IgG results from both TI and TD processes (14). Since the antigen-specific T cell response is still fully functional at the onset of sepsis (47), we assumed that the class switched IgG response was mainly directed at the invasive bacteria.…”
Section: A Strong Induction Of Total Serum Igg During Sepsis Was Not mentioning
confidence: 97%
“…In fact, Mohr et al have shown that B cell priming with defined antigens is defective in sepsis (13). By contrast, we and other research groups have shown that sepsis induces high concentrations of serum IgM and IgG antibodies of unknown specificities (13,14). Since these may be responsible for the observed antibodymediated protection, we set out to examine their antigen specificities in a mouse model of abdominal sepsis.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations